A Neoconservative Consensus in Russia?: Main Components, Factors of Stability, Potential of Erosion. Issue 4 (3rd September 2017) - Melville, Andrei
Abstract : This article analyzes the ideational consensus that has taken shape in contemporary Russian politics, including its key components, and factors both of stability and of potential erosion. Noting the extraordinary durability of this consensus, which is supported by factors including the duration of the regime itself, its support among elites and the bureaucracy, effective mobilizational propaganda and conservative orientations among the middle classes and dominant public opinion, the author draws attention to several factors – as yet less evident – that may in the future change the situation. Among these are the volatility of public opinion, potential intra-elite dynamics, and the internal contradictions of the neo-conservative idea itself.